The Local Rice Varieties' Growth and Yield Reaction to Drought Conditions - Dadang Sumardi; Popi Septiani; Husna Nugrahapraja; Chindy Ulima Zanetta; Tati Kristianti (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Local rice cultivars are traditionally developed and maintained through farmer-based agricultural practices. Identifying traits associated with drought tolerance in local rice germplasm is essential for the development of high-yielding, drought-resistant varieties. Therefore, this study aimed to evaluate the drought tolerance characteristics of local rice cultivars from West Java, Indonesia. Fifteen local rice cultivars were collected from three locations: Tanjungsari District (Sumedang Regency), Ciletuh District (Sukabumi Regency), and Pandeglang Regency. The experiment was arranged in a randomized block design with two treatment factors and three replications. The ten local rice cultivars evaluated exhibited different responses to variations in soil water content relative to field capacity. Based on the Drought Sensitivity Index (DSI), five cultivars were classified as sensitive, four as moderately tolerant, and one as tolerant to drought stress. Under optimal water availability, the Ampera, NN Banten, and Rancung cultivars demonstrated high grain yield potential. However, the Rancung cultivar was found to be susceptible to drought stress. In contrast, the Huma Hideung Ciletuh cultivar was classified as drought-tolerant because it showed only minor reductions in grain weight and grain number under drought conditions compared with optimal water availability.